2019
DOI: 10.3390/agronomy9070358
|View full text |Cite
|
Sign up to set email alerts
|

Different LED Light Intensities and 6-Benzyladenine Concentrations in Relation to Shoot Development, Leaf Architecture, and Photosynthetic Pigments of Gerbera jamesonii Bolus In Vitro

Abstract: A mixture of red and blue light-emitting diodes (LEDs; at a ratio of 7:3, respectively) were used to analyze the effects of different photosynthetic photon flux densities (PPFDs) (40, 80, and 120 µmol m−2 s−1 hereafter known as LED 40, 80, and 120, respectively) on the micropropagation of Gerbera jamesonii Bolus shoots. The experiment also examined the effect of 6-benzyladenine (BA) in 1, 2.5, and 5 µM concentrations in the media. Biometrical observations and analyses of leaf morphometry and photosynthetic pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…Studies of other researchers have shown that the combination of red and blue LEDs enhances Mentha and Fragaria growth as compared to other monochromatic spectra (Nhut et al, 2003;Gupta and Jatothu, 2013;Sabzalian et al, 2014). Also, the results presented by Pawlowska et al (2018) and Cioć et al (2019) showed that combination of red and blue LEDs (7:3) could be an effective and affordable tool for modifying the potential of Gerbera jamesonii Bolus plants for shoot multiplication and for the control plant morphogenesis and photosynthetic pigment content.…”
Section: Chlorophyll a Fluorescencementioning
confidence: 87%
“…Studies of other researchers have shown that the combination of red and blue LEDs enhances Mentha and Fragaria growth as compared to other monochromatic spectra (Nhut et al, 2003;Gupta and Jatothu, 2013;Sabzalian et al, 2014). Also, the results presented by Pawlowska et al (2018) and Cioć et al (2019) showed that combination of red and blue LEDs (7:3) could be an effective and affordable tool for modifying the potential of Gerbera jamesonii Bolus plants for shoot multiplication and for the control plant morphogenesis and photosynthetic pigment content.…”
Section: Chlorophyll a Fluorescencementioning
confidence: 87%
“…Similarly, NAA proved to stimulate isoflavone production in Genista tinctoria L. calli at 5.0 mg•L −1 when applied jointly with 0.5 mg•L −1 cytokinin [45]. Perhaps using a light factor instead of PGRs combination would allow for even more effective control of pigment synthesis in the bleeding heart, as reported by Cioć et al in gerbera [44].…”
Section: Biosynthesis Of Metabolites In Callusmentioning
confidence: 70%
“…Cytokinins play an important role in the development and structural differentiation of chloroplasts [15]. Consequently, increased BA concentration raised the content of chlorophyll and carotenoids in the leaves of Gerbera jamesonii Bolus cultured in vitro [44]. Callus cultures of the bleeding heart, however, seem to respond differently since the highest levels of chlorophylls and carotenoids were found in the experimental combination with the lowest concentrations of PGRs.…”
Section: Biosynthesis Of Metabolites In Callusmentioning
confidence: 99%
“…For Chrysanthemum × grandiflorum, the final effect of light conditions varied depending on the developmental phase of microshoots (Kurilcik et al, 2008). A significant interaction was also observed between light intensity and concentration of N-benzyladenine in the culture medium on the shoot proliferation and development, leaf architecture, and content of photosynthetic pigments in Gerbera jamesonii and Myrtus communis cultured in vitro (Cioć et al, 2018, Cioć et al, 2019.…”
Section: Organogenesis In Vitromentioning
confidence: 91%